REKONSTRUKSI DUAL BANKING SYSTEM: KEBERADAAN PRINSIP-PRINSIP SYARIAH PERBANKAN DALAM SISTEM HUKUM PERBANKAN NASIONAL - Kristianti, Dewi Sukma (Faculty of Law, Parahyangan Chatolic University, 2015)
The legal practice of Islamic (Sharia) economics in the real sector of Indonesiaâs national economic development by way of various institutions or Islamic (sharia-based) economic centers has had a positive impact on the growth and development of the national economy. The practice is based on Islamic principles, which have been shaped into a wide variety of regulations or legislation in effect. In the legal concept of Sharia economics, the state as represented by the government that implements Sharia-based economic practices must apply the principles of Islamic economics to achieve the goal of Islamic economic law. The purpose of this Sharia economic law emphasizes the benefits for society based on the balance and fairness thus attained to present a showcase of the politics involved in Islamic economic law. The actual reality of legislation in Sharia-based economic activities issued by the government still falls decidedly short of expectations when compared to conventional economic activities and legal certainty in other countries, due to the role that Islamic economic law plays in determining the governmentâs political direction and ways of formalizing Islamic economic law in Indonesia.